Morin attenuates oxidized low‐density lipoprotein‐mediated injury by inducing autophagy via activating AMPK signalling in HUVECs. (9th September 2019) - Zhang, Xiaodong; Han, Xiping; Zhang, Peng; Zhou, Tingting; Chen, Yun; Jin, Jian; Ma, Xin
Abstract: Endothelial dysfunction is a precursor of cardiovascular disease, and oxidized low‐density lipoprotein (ox‐LDL) has been implicated in the development of atherosclerosis by directly targeting endothelial cells. Morin, a natural flavonol, has been shown to protect endothelial cells from dysfunction. The present study was designed to evaluate the effect of morin on ox‐LDL‐induced injury and to investigate the underlying molecular mechanisms in human umbilical vein endothelial cells (HUVECs). The results showed that morin alleviated ox‐LDL‐induced endothelial injury and promoted the viability of HUVECs exposed to ox‐LDL. Morin significantly inhibited the oxidative stress induced by ox‐LDL by inhibiting the production of reactive oxygen species and malondialdehyde, and downregulating the level of superoxide dismutase. Moreover, morin markedly attenuated the overexpressed mRNA levels of the inflammatory factors interleukin (IL)‐1β, IL‐6, and the adhesion molecules ICAM‐1 and VCAM‐1 induced by exposure to ox‐LDL. We found that morin attenuated ox‐LDL‐induced injury in HUVECs by inducing autophagy. The protective effects of morin against ox‐LDL‐induced injury were dramatically reversed by chloroquine phosphate (CQ) treatment. Furthermore, morin up‐regulated the expression of p ‐AMPK and down‐regulated the level of p ‐mTOR in HUVECs exposed to ox‐LDL, and this was significantly reversed by the AMPK inhibitor Compound C (CC). Taken together, our results demonstrated that morin attenuates ox‐LDL‐mediated injury by inducing autophagy via activating AMPK signalling in HUVECs.